The Management of Salivary Fistulas - Belcastro, Alexandra; Reed, William; Puscas, Liana (Seminars in Plastic Surgery, 2022)
Postoperative salivary fistula is an especially undesirable complication because it can be difficult to address, may delay postoperative radiation, and always delays enteral nutrition. Patients who are malnourished, have already undergone radiotherapy, or are hypothyroid are at higher risk of developing this problem. Conservative measures work in most patients, but a significant percentage of patients require intervention beyond pressure dressings and tincture of time. Medications, hyperbaric oxygen therapy, and surgical intervention may be required when fistulas do not heal in a timely manner. Decisions about the approach and timing of more aggressive interventions are part of the art of medicine since definitive scientific protocols are lacking.
Keywords: postoperative; salivary fistula; complication